Diagnosis and management of tuberculous paraplegia with special reference to tuberculous radiculomyelitis. - Freilich, D (1979)
Paraplegia occurred in eight of 17 patients with central nervous system tuberculosis. In six of these paraplegia was the presenting feature. Paraplegia may complicate tuberculous meningitis, or vertebral tuberculosis, but it may also occur, as in three of our cases, as a primary localised spinal tuberculous radiculomyelitis. These cases are presented in relation to the concept that paraplegia complicating these forms of tuberculosis is caused by radiculomyelitis.